Secret to Success: Securing Petronas Vendor Development Program (VDP) - M. S. M., Sani; Siti Norazila, Zahari; N. I. M., Azmi; S., Musa (Knowledge Transfer Centre, USM, 2016)

(untitled)
Small and Medium Industries (SMIs) consist of companies or enterprise that supply manufacturing services with sales turnover less than RM25 million individual annually and employed not exceeding 150 full time workers. FM Plastics Industries Sdn. Bhd. is one of the SMIs companies that owned by 100% bumiputera with capacities of 15 employees that supply Tubular Tubing Rolls. FM Plastic Industries Sdn. Bhd. managed to secure and officially be appointed as a vendor for PETRONAS under the Vendor Development Programme (VDP) by supplying Polyethylene heavy duty bagging rolls to Polyethene Malaysia Sdn. Bhd. (PEMSB) known as subsidiary company for PETRONAS. Many initiatives have been taken by FM Plastic Industries in order to fulfil the requirement as PETRONAS vendor including to implement the requirement of quality management system ISO9001:2008 towards developing a sound quality management. The high quality of their product also being the core to secure the vendor because their product will be through seven types of testing before being supply; physical test, thickness test, dart impact test, sealing test, friction test, composition and analyzer test and drop test. Continuous improvement provides by the company also being play a vital role to secure the vendor. FM Plastic Industries joined together with Universiti Malaysia Pahang in Knowledge Transfer Programme under the project of Control System Technology Transfer, Design of Plastic Printing and Engineering Management in Industrial Management is an initiative to improve the quality of their product lead to build confidence and expectation for PETRONAS to appoint the company as a vendor.